Leishmania donovani evades Caspase 1 dependent host defense mechanism during infection - Saha G.; Khamar B.M.; Singh O.P.; Sundar S.; Dubey V.K. (My University, 2025)
Significant advances have been made in understanding the regulation of inflammasomes and its involvement in innate immunity during pathogenic infections. Inflammasome activation is a tightly regulated process that provides defense against pathogenic infection and important for inflammatory response. Very few studies on the involvement of NLRP3 inflammasome protein complex have been reported in leishmanial infections with contradictory results and without much mechanistic insights. However, the role of NLRP3 inflammasome and its components has not been well deciphered in Leishmania donovani infection. Here we report for the first time a detailed mechanism and plausible impairment of caspase 1 activation during L. donovani infection leading to the survival of these parasites inside the host cells. Low mRNA expression of pro-caspase 1 and lack of caspase 1 maturation were observed after infection, hindering the processing of pro-IL-1β and pro-IL-18 into their mature counter parts. Further, siRNA mediated knock-down of caspase 1 in macrophage cells (THP-1) resulted in significantly higher parasitic burden validating the importance of caspase 1 in the host defense mechanism. Taken together, our data suggests that the parasite inhibits caspase 1 activation to evade the inflammatory nature of pyroptosis. © 2018